ANALISIS KUAT TEKAN GREEN CONCRETE FC 20 MPa MENGGUNAKAN BIJI PLASTIK PETE (POLYETHYLENE TEREPHTHALATE) - Widyarini, Galih; Herdiarti, Etika; Azizah, Nur; Mukti, Galang Wicaksono (Bangun Rekaprima, 2024)
Concrete is a building material consisting of a mixture of coarse aggregate, fine aggregate, cement, water and other additional materials (Firdaus, 2019). Concrete materials come from nature (gravel, sand and aggregate) which will eventually run out because they cannot be renewed. Therefore, the use of concrete materials needs to be innovated to become green concrete or environmentally friendly concrete. Environmentally friendly concrete is made using waste or comes from industrial waste materials. One of them is replacing aggregate with materials that do not damage the environment, such as Polyethylene Terephthalate (PETE) plastic pellets. PETE plastic pellets are a type of plastic material that has wrinkle-free fibers. This material is often used for packaging food and drinks such as bottles of soft drinks, mineral water and so on. The aim of this research is to determine the influence and trend of compressive strength of fc'20 MPa concrete on replacing some of the coarse aggregate with PETE (Polyethylene Terephthalate) plastic pellets varying 10%, 20% and 30%. The research method used was to make cylindrical test objects of each variation and then test them at the age of 7 days, 14 days and 28 days. The compressive strength test results for concrete variations of 10% PETE at 7 days, 14 days and 28 days were 21.84 MPa; 22.78 MPa and 24.35 MPa. In the concrete test variation of 20% PETE aged 7 days, 14 days and 28 days was 21.03 MPa; 22.09 MPa and 23.21 MPa. The compressive strength test for concrete variations of 30% PETE aged 7 days, 14 days and 28 days was 20.22 MPa; 20.71 MPa; and 20.95 MPa. These results show that the test object produces concrete compressive strength exceeding FC 20 MPa with an increasing trend from 7 days - 28 days.